2017
DOI: 10.1093/nar/gkw1367
|View full text |Cite
|
Sign up to set email alerts
|

PRMT5 regulates IRES-dependent translation via methylation of hnRNP A1

Abstract: The type II arginine methyltransferase PRMT5 is responsible for the symmetric dimethylation of histone to generate the H3R8me2s and H4R3me2s marks, which correlate with the repression of transcription. However, the protein level of a number of genes (MEP50, CCND1, MYC, HIF1a, MTIF and CDKN1B) are reported to be downregulated by the loss of PRMT5, while their mRNA levels remain unchanged, which is counterintuitive for PRMT5's proposed role as a transcription repressor. We noticed that the majority of the genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 67 publications
(93 reference statements)
7
85
2
Order By: Relevance
“…We found that the two techniques were mostly orthogonal for both methyl peptide identification and LFQ quantitation, demonstrating that comprehensive measurement of the protein methylome requires multiple methyl peptide enrichment strategies. Although SCX and IAP enrich different methyl peptides, both SCX and IAP peptides were enriched for the GO annotation RNA binding, consistent with the known function of protein methylation (11,24,(43)(44)(45)(46)(47) (Fig. 1D).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…We found that the two techniques were mostly orthogonal for both methyl peptide identification and LFQ quantitation, demonstrating that comprehensive measurement of the protein methylome requires multiple methyl peptide enrichment strategies. Although SCX and IAP enrich different methyl peptides, both SCX and IAP peptides were enriched for the GO annotation RNA binding, consistent with the known function of protein methylation (11,24,(43)(44)(45)(46)(47) (Fig. 1D).…”
Section: Discussionsupporting
confidence: 72%
“…Gene ontology analysis of methyl peptides identified by SCX and IAP demonstrated that both techniques were highly enriched for RNA binding proteins ( Fig. 1D), in agreement with known properties of methyl proteins (11,24,(43)(44)(45)(46)(47). In addition, IAP enriched proteins related to DNA binding and transcription factor binding, whereas SCX enriched proteins related to nucleoside-triphosphatase activity and hydrolase activity.…”
Section: Scx and Iap Enrich Methyl Peptides And Target Different Subssupporting
confidence: 74%
See 1 more Smart Citation
“…In turn, RIOK1—as part of the PRMT5 complex—promotes the translation of c-Myc transcripts (26). Hence, it is not surprising that RIOK1 is overexpressed in myriad malignancies (145).…”
Section: Discussionmentioning
confidence: 99%
“…Although arginine methylation has been mostly associated with changes in protein-protein interactions (50,51), there are previous examples of direct modulation of RNA-protein binding in mammalian cells (52)(53)(54). PRMTs have previously been shown to regulate the RNA affinity of target RBPs in other systems (55,56).…”
Section: Discussionmentioning
confidence: 99%